Puzzling Out Synaptic Vesicle 2 Family Members Functions - Bartholome, Odile; Van den Ackerveken, Priscilla; Sánchez Gil, Judit; de la Brassinne Bonardeaux, Orianne; Leprince, Pierre; Franzen, Rachelle; Rogister, Bernard (Frontiers in Molecular Neuroscience, 2017)
Synaptic vesicle proteins 2 (SV2) were discovered in the early eighties, but the clear demonstration that SV2A is the target of efficacious anti-epileptic drugs from the racetam family stimulated efforts to improve understanding of its role in the brain. Many functions have been suggested for SV2 proteins including ions or neurotransmitters transport or priming of synaptic vesicles. Moreover, several recent studies highlighted the link between SV2 and different neuronal disorders such as epilepsy, schizophrenia, Alzheimer’s or Parkinson’s disease. In this review, we will summarize our present knowledge on SV2A function(s) and its potential role(s) in the pathophysiology of various brain disorders.